Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper, 2010)
This paper examines the performance of emerging market economies (EMs) during the recent global crisis and draws policy conclusions. It considers how EMs were affected by the initial impact of the crisis, examines the extent to which they were able to undertake countercyclical policies to moderate the impact, and highlights factors that have influenced the pace and timing of their recovery. Finally, it considers policy challenges facing EMs as the crisis subsides. This paper sheds light on the role of reserves in crises, and provides contextual background for work on the future financing role of the IMF.